Pengaruh Content Marketing, Sosial Media, Dan Word Of Mouth (WOM) Dalam Meningkatkan Brand Awareness Pada Digital Print Finsa Studi Kasus Digital Print Finsa Samban - Erla Julian Ferdiana; Jaya Ramadaey Bangsa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the influence of content marketing, social media and word of mouth (WOM) in increasing brand awareness among Finsa Samban Digital Print consumers. The influences you want to know are direct and indirect influences. This research uses a quantitative method with a descriptive research model which presents an accurate, systematic and factual description of a situation or phenomenon on variables through hypothesis testing by distributing questionnaires. This research used a sample of 96 respondents. Samples were taken using a purposive sampling method using non-probability with characteristics of a minimum age of 17 years and having used a product or service from Digital Print Finsa at least once. The test tools used are research instrument tests, classical assumption tests and multiple regression analysis tests. From the results of this test it can be concluded that marketing content has a significant direct influence on brand awareness. Social Media has an indirect influence in the research results in the T Test which is stated to have no significant effect on brand awareness. The results of the study on word of mouth (WOM) have a significant direct influence on brand awareness on Digital Print Finsa Samban.